In silico mutations of TEM-1 β-lactamase show changes in structure and drug-enzyme affinity binding by molecular docking - Molina Mora, José Arturo (2016)
Bacterial resistance refers to bacteria capacity to evade antibiotic action, which constitutes a public health issue. This resistance is given by β-lactamase enzymes that break the drug rings and alter its function. To counteract this effect, some β-lactamase inhibitors, that have a higher affinity and irreversibly bond, have been used. However, as a consequence of selective pressure, some mutations have caused enzyme-drug affinity changes. TEM-1 is a serine- β-lactamase in which this process has been proved, giving particular interest for evaluating how these mutations affect drug-enzyme binding force. When making simulations with four mutations M182T, V184A, T160H and A224V and undertaking molecular docking, a change in the affinity pattern was observed, aiding enzyme-antibiotic bindging rather than enzyme-inhibitor bindging, which would explain lab results in which the use of β-lactamase inhibitors has not been effective. Besides, with the purpose of exploring inhibition alternatives in the enzyme, simulations with one BLIP (β-lactamase inhibitor protein) were carried out, showing that the bond between β-lactamase and BLIP alters drug access to an active site.